How perceptions and information about women's descriptive representation affect support for positive action measures. Issue 2 (March 2023) - Coffé, Hilde; Reiser, Marion
Based on the German Longitudinal Election Study (2016), we explain citizens' support for measures to increase women's descriptive representation in parliament. Despite women's underrepresentation, we find little support for positive action measures, and in particular for legal gender quotas. Binary logit analyses show that support for the introduction of positive action measures is not affected by citizens' perceptions about the share of female members of parliament. However, experimental data reveal that receiving information about women's actual proportion in parliament has an impact on citizens' support for gender quotas, in particular among those who overestimate women's representation. Once they learn that the actual share is lower than they thought, they are more likely to support the introduction of quotas. This indicates that support for positive action measures can be changed through providing the correct information.